Access and Financial Burden for Patients Seeking Essential Surgical Care in Pakistan. Issue 1 (20th December 2022) - Samad, Lubna; Ashraf, Muhammad Nabeel; Mohammad, Ammar Ali; Fatima, Irum; Fowler, Zachary; Albutt, Katherine; Latif, Asad; Meara, John G.; Pigeolet, Manon
Background: Pakistan is a lower middle-income country in South Asia with a population of over 220 million. With the recent development of national health programs focusing on surgical care, two areas of high priority for research and policy are access and financial risk protection related to surgery. This is the first study in Pakistan to nationally assess geographic access and expenditures for patients undergoing surgery. Methods: This is a cross-sectional study of patients undergoing laparotomy, cesarean section, and surgical management of a fracture at public tertiary care hospitals across the country. A validated financial risk protection tool was adapted for our study to collect data on the socio-economic characteristics of patients, geographic access, and out-of-pocket expenditure. Results: A total of 526 patients were surveyed at 13 public hospitals. 73.8% of patients had 2-hour access to the facility where they underwent their respective surgical procedures. A majority (53%) of patients were poor at baseline, and 79.5% and 70.3% of patients experienced catastrophic health expenditure and impoverishing health expenditure, respectively. Discussion: A substantial number of patients face long travel times to access essential surgical care and face a high percentage of impoverishing health expenditure and catastrophic health expenditure during this process. This study provides valuable baseline data to health policymakers for reform efforts that are underway. Conclusions: Strengthening surgical infrastructure and services in the existing network of public sector first-level facilities has the potential to dramatically improve emergency and essential surgical care across the country.